Influence of sequence of elemental addition on phase evolution in nanocrystalline AlCoCrFeNi: Novel approach to alloy synthesis using mechanical alloying. (15th July 2017) - Vaidya, Mayur; Prasad, Anil; Parakh, Abhinav; Murty, B.S.
Abstract: The conventional way to form a multicomponent alloy requires mixing individual elements in a single step. Phase formation, therefore, is governed by inherent thermodynamic and kinetic factors of the system. We propose here a new approach for multicomponent alloy synthesis, which involves step by step addition of constituent elements. In the present work, this is illustrated through the formation of nanocrystalline equiatomic AlCoCrFeNi by mechanical alloying. For example, first, binary CoNi is formed by milling elemental Co and Ni powders. In the subsequent steps, Fe, Cr and Al are added to form ternary (CoNiFe), quaternary (CoNiFeCr) and quinary (CoNiFeCrAl) alloy, respectively. Three different classes of binaries have been selected as initial phases, namely, B2 (AlNi, AlCo and AlFe), BCC (FeCr) and FCC (CoNi and FeNi). Remaining constituent elements are added step-wise in varying sequences and equiatomic AlCoCrFeNi is obtained in the concluding step. The final AlCoCrFeNi alloy at the end of each sequence has varied fractions of BCC and FCC phases. For instance, AlNi + Co + Fe + Cr sequence is single phase BCC, whereas the sequence FeNi + Co + Cr + Al results in a mixture of BCC (75%) and FCC (25%) phases. The extent to which a particular element stabilizes a structure (BCC/B2/FCC) has also been elucidated. Graphical abstract: Highlights: A novel approach, termed sequential alloying, for multicomponent alloy synthesis is proposed. It involves stepwise addition of constituent elements, unlike the conventional way of mixing in a single step. Nanocrystalline equiatomic AlCoCrFeNi is processed by mechanical alloying using 12 diverse sequences of elemental addition. The quinary AlCoCrFeNi obtained at the end of each sequence has varied fractions of BCC and FCC phases. Sequence AlNiCoFeCr results in single phase BCC, whereas both BCC (75%) and FCC (25%) phases are observed in FeNiCoCrAl.